Achievement of the ESC recommendations for secondary prevention of cardiovascular risk factors in high-risk patients with type 2 diabetes: A real-world national cohort analysis. (15th April 2023) - Salem, Ahmed M.; Harris, Daniel; Bray, Jonathan J.H.; Obaid, Daniel R.; Stephens, Jeffrey W.; Halcox, Julian
Abstract: Aim: To assess compliance with European Society of Cardiology (ESC) secondary prevention recommendations in a nationwide contemporary population with diabetes mellitus (DM) and coronary artery disease. Method: We conducted a retrospective observational study using linked health data in patients across Wales with DM undergoing percutaneous coronary intervention (2012–2017). The follow-up was for one year. We analysed the clinical characteristics, medications, target levels for HbA1c, low-density lipoprotein cholesterol (LDL-C), non-high-density lipoprotein cholesterol (non-HDL-C) and blood pressure against the ESC prevention guidelines. Results: Overall, 3478 patients with diabetes had available data at 1-year post-PCI. Only 43% had HbA1c levels <53 mmol/L, but 81% had blood pressure < 140/80 (current ESC targets). Prescribing frequency of the newer hypoglycaemic agents (glucagon-like peptide-1 receptor agonists and sodium-glucose co-transporter 2 inhibitors) was suboptimal, with a higher rate in patients with HbA1c ≥53 mmol/mol. Only 51% & 27% of the patients had LDL-C levels <1.8 &1.4 mmol/L (2016 & 2019 guidelines recommendations respectively), and 55% & 34% had non-HDL-C levels <2.6 & 2.2 mmol/L (2016 & 2019 guidelines respectively). Of the uncontrolled LDL-C patients, 42% (2016 target) and 35% (2019 target) were prescribed high-intensity statins. Females were more likely to have LDL-C targets above the recommended level. Conclusion: Achievement of ESC treatment goals in this very-high risk cohort for DM and hyperlipidaemia was far from optimal, with a low prescription rate of the guidelines-recommended therapy. Target goals for hypertension were met more frequently. An up-to-date analysis reflecting the current practice against the most recent guidelines is warranted. Highlights: There is a clinical gap between real-life CV risk factors management and the recommendations laid in the guidelines. P rescription rate of medications with previous personal experience is higher than relatively newer ones. Females have a lower probability of achieving the recommended LDL-C targets and is less likely to be followed up. Secondary prevention optimization is more efficient when managed by specialists rather than primary care physicians